Study of Repulsive Interaction in Ionin Crystals - Roy, R.S. (Asian Journal of Chemistry, 2010)
The repulsive interaction in an interaction potential of ion-ion interaction in alkali halides in molecular and crystalline states has been presented. The different contributions arising from the polarization forces and van der Waals interactions are investigated for these molecules. In crystal binding, the contributions arising from the van der Waals dispersion forces and the repulsive interaction between nearest neighbours and next nearest neighbours have also been taken into account. The result of various spectroscopic constants, cohesive energy and bulk modulus for a number of alkali halides are in excellent agreement with corresponding experimental results.